Is it fun or is it hard? Studying physician-related attributes of shared decision-making by ranking case vignettes - Laura Spinnewijn; Johanna Aarts; Didi Braat; Nikolaj Baranov; Klaas Sijtsma; Jules Ellis; Fedde Scheele (Elsevier, 2023)
Objective: This study investigated provider-related attributes of shared decision-making (SDM). It studied how physicians rank SDM cases compared to other cases, taking 'job satisfaction' and 'complexity' as ranking criteria. Methods: Ten vignettes representing three cases of SDM, three cases dealing with patients' emotions and four with technical problems were designed to conduct a modified ordinal preference elicitation study. Gynaecologists and trainees ranked the vignettes for 'job satisfaction' or 'complexity'. Results were analysed by comparing the top three and down three ranked cases for each type of case using exact p-values obtained with custom-made randomisation tests. Results: Participants experienced more satisfaction significantly from performing technical cases than cases dealing with emotions or SDM. Moreover, technical cases were perceived as less complex than those dealing with emotions. However, results were inconclusive about whether gynaecologists find SDM complex. Conclusion: Findings suggest gynaecologists experience lower satisfaction with SDM tasks, possibly due to them falling outside their comfort zone. Integrating SDM into daily routines and promoting culture change favouring dealing with non-technical problems might help mitigate issues in SDM implementation. Innovation: Our novel study assesses SDM in the context of task appraisal, illuminating the psychology of health professionals and providing valuable insights for implementation science.